Vision-based control of robot - Li, Jianwei. (2011)
Today, the use of robotic systems has significantly contributed to the increase in speed and precision of automated tasks in industrial manufacturing process. Due to the advancement of technology, it becomes highly desirable to make robots intelligent so that they can function independently with minimal inputs from users.